Reasons for participation and satisfaction in physical activity, physical exercises, and sports - Garita Azofeifa, Elmer (2006)
Motivation in physical activity constitutes a multidimensional psychological characteristic that is influenced by the person’s internal aspects (preferences, desires, fears, etc.) and his/her experiences in the external environment (social acceptance, friends, skills, etc.).  In a period in which physical activity is globally increasing among people of all ages, it is important for physical educators, sports trainers, or physical instructors to know the main reasons for their trainees to exercise with the purpose of preparing ideal workout plans that would help them continue exercising.  These plans should encourage subjects to enjoy and be satisfied with their participation, therefore, extending their active life cycle and avoiding quitting, which are closely related to a sedentary lifestyle and the risk of having chronic and degenerative diseases.  Consequently, children prefer to exercise to have fun and make friends, adolescents to compete and make friends, college students for adventure and fun, adults to have regular physical activity, and senior citizens to obtain health benefits.  Women are motivated by their appearance and social reasons, while men do it for competition and status.  Subjects who practice sports are motivated by competition, while those who exercise do it for body image.  The more physical activity is practiced the more value is given to competition.  Finally, having fun, competing, learning skills, and being in good physical condition are the most relevant reasons for American, European, and Asian subjects to participate in physical activity.  This research was conducted with the purpose of letting professionals of human movement sciences know the variables that determine the reasons for subjects of distinctive ages, gender, culture, and level of activity to participate in the different types of physical activities.